Toxicity of Barringtonia asiatica Seed Extract Against Chilo sachariphagus - Rohendi Rohendi; Danar Dono; Andang Purnama (CROPSAVER, 2019)
Barringtonia asiatica is one of the plants that the seeds extracts has insecticidal properties. However, the bioactivity of this seed extract has not been tested against Chilo sacchariphagus larvae which is the main pests in sugar cane. The treatment was carried out at several levels of concentration of methanolic seed extract of B. asiatica. The 15 cm of fresh sugarcane shoot dipping into the extract solution in some second. After the solution of extract on the sugarcane shoot dried, the first instar of larvae infested to the sugarcane shoot and then put into 20 cm test tube with 3 cm of diameter.  The duration of feeding on treated sugarcane shoot was two days and on the following day the larvae were fed on sugar cane shoots until the survived larvae reached the 5th instar. The results of the experiment indicated that B. asiatica seed extract was toxic to C. sacchariphagus with an LC50 value of 0.398% at 16 days after treatment. Besides toxic, B. asiatica seed extract also has atifeedant activity, and inhibits the growth of immature of C. sacchariphagus in all tested concentrations.Keyword: Toxicity, antifeedant, lethal concentration, Barringtonia asiatica, Chilo sachariphagus